沈降反応によるトウモロコシ類縁関係判別法に関する研究 : 第4報 免疫に用いた蛋白量と沈降反応との関係 - 浦野 啓司; 荒井 好邦 (日本作物學會紀事, 1956)
(1) The relation between quantities of antigen made from corn pollen and its precipitin reaction was examined. Four levels of antigen quantity, 32.44mg, 48.66mg, 52.94mg, and 81.10mg as protein, were tested. (2) From the results, it was elucidated that the larger the quantity of antigen used, the clearer becomes the precipitin reaction.